Women marginalization and political corruption in Margaret Atwood's The Handmaid's Tale - Al Ogaili, Thamer Amer Jubouri; Mani, Manimangai; Kaur, Hardev; Awang, Mohammad Ewan (American Research Institute for Policy Development, 2019)
This article examines the function of dystopia in Margaret Atwood‘s The Handmaid‘s Tale(1986). The study will mainly focus of the issues of women marginalization and political corruption by approaching the dystopia qualities in the novel. On the one hand, women marginalization is going to be identified be discussing the inferior position in society as depicted in the novel. This is because women are exploited for domestic drudgery. They lose their equality since there is no opportunity allowed for them to be as independent as men. On the other hand, the issue of political corruption will be explored to sustain the study‘s concern with novel‘s dystopian world. Accordingly, both women marginalization and political corruption will be elaborated as the dystopian peculiarities which contradict Atwood‘s style that seeks utopia society and a world that seems to be utterly corrupted. Therefore, postfeminism is going to be applied as the study‘s theoretical framework, whereby women marginalization will be discussed in politically corrupted peripheries